THE FACTORS AFFECTING ON THE SUCCESS OF IMPLEMENTING TOTAL PRODUCTIVE MAINTENANCE IN THE MANUFACTURING COMPANY (NS BLUESCOPE VIETNAM). - Pham Van Tai (PhD), Phan Cao Huy (MBA) (International Journal of Research Science and Management, 2017)
The competition in business environment becomes more strictly, manufacturers must introduce lots of new products on the high quality level with suitable price. Thus, new technologies have been applied, manufacturing systems become more complex. Therefore, a new strategy for maintenance such as Total productive maintenance (TPM) becomes really necessary. Many organizations have implemented TPM to increase the effectiveness of manufacturing system. However, implementation of TPM still meets a lot of drawbacks. This paper, will focuses on the factors can help implementing the TPM successfully in manufacturing organizations. This study is an attempt to look at the successful factors of TPM implementation at NS BlueScope Vietnam, a steel manufacturer